Effectiveness of Impeachment Against Deputy Regent of Gorontalo Regency - Luksiana Lasimpala; Lisnawaty W. Badu; Novendri M. Nggilu (Universitas Negeri Gorontalo, 2021)
The purpose of this research is to know and analyze the Legal Regulation of The Impeachment of Regional Heads and/or Deputy Heads of Regions according to The Provisions of Law No. 23 of 2014 on Local Government and the effectiveness of impeachment against the deputy Regent of Gorontalo Regency. The type of research used by researchers in the preparation of this study is to use normative research types that are supported by the existence of field data (empirical) using 2 (two) approaches, namely the Legislative And Case Approach. The results of this study show that the effectiveness of impeachment against the deputy Regent of the Gorontalo Regency is influenced by 3 (three)factors that affect the effectiveness of dismissal against the deputy Regent of the Gorontalo Regency, namely: the legal factor. alone, where there is no normative framework that regulates the law of dismissal events in the head of the region, second, law enforcement factors, namely regarding the competence of judges in the break the case and the unclear involvement of legal counsel (advocate), third, the legal culture factor characterized by the disobedience of the Ministry of Home Affairs to the deadline which has been made imitatively in Law 23 of 2014 concerning Local Government.